IMPLEMENTASI ALGORITMA A-STAR PADA ROKET KENDALI SENJATA RUDAL DALAM GAME WEAPON WAR BERBASIS UNITY - , (Seminar Nasional Informatika (SENATIKA); 2023: Prosiding Seminar Nasional Informatika (SENATIKA) - IV, 2024)
This research presents the implementation of the A-Star algorithm in the missile rocket control system of the Unity-based game Weapon War. The algorithm is used to calculate the shortest path between the enemy and the target, enabling the missile rocket control system to move intelligently and efficiently. Performance evaluations demonstrate a significant improvement in the intelligence of the enemies utilizing the A-Star algorithm, showcasing enhanced abilities to avoid obstacles and efficiently reach their targets. The research contributes to the development of more challenging and entertaining games by enhancing the artificial intelligence of enemy characters in the context of missile rocket control. The implemented A-Star algorithm in the Unity-based Weapon War game serves as a foundation for the creation of more captivating game experiences.